IDENTIFIKASI KENDALA DALAM STRATEGI FUNDRAISING WAKAF ONLINE DI GLOBAL WAKAF SURAKARTA - Karnawijaya, Ning; Maharani, Deshinta (Program Studi Manajemen Zakat dan Wakaf, 2020)
Fundraising is an important activity in maintaining the sustainability of a waqf institution. Based on field data from observations and interviews, as well as various literatures, this study aims to identify the constraints in the online waqf fundraising strategy at Global Wakaf Surakarta and the efforts that can be made in dealing with these constraints. The analysis was carried out with a qualitative descriptive approach. Fundraising constraints faced by the Global Wakaf Surakarta institution are when the fundraising objectives have not been maximally realized, namely the inadequate method of collecting funds, there are still few wakifs who make donations, lack of ability to improve the image of waqf institutions, and lack of ability to maintain continuity of wakifs. Constraints in the fundraising strategy are also seen in the application of fundamental principles, namely the lack of ability to ask the community to act as wakif, lack of capacity to expand relationships and networks, the lack of ability to sell products / programs offered, and the difficulty of increasing public trust to be donated in the Global Wakaf Surakarta institute. Strategies that can be carried out to deal with fundraising constraints in Global Wakaf Surakarta are to pay attention the fundamental elements, namely meeting wakif needs, product development (programs), promotion with a wider reach, and maintaining or increasing the number of regular wakifs so that the program that has not yet been implemented immediately. Fundraising merupakan kegiatan penting dalam menjaga keberlangsungan sebuah lembaga wakaf. Berbasis pada data lapangan dari hasil observasi dan wawancara, serta berbagai literature, kajian ini bertujuan untuk mengidentifikasi kendala-kendala dalam strategi fundraising wakaf online di Global Wakaf Surakarta dan upaya yang dapat dilakukan dalam menangani kendala-kendala tersebut. Analisis dilakukan dengan pendekatan deskriptif kualitatif. Kendala-kendala fundraising yang dihadapi lembaga Global Wakaf Surakarta adalah ketika tujuan fundraising belum terwujud secara maksimal yaitu belum maksimalnya cara pengumpulan dana, masih sedikitnya wakif yang melakukan donasi, kurangnya kemampuan dalam peningkatan citralembaga wakaf, dan kurangnya kemampuan dalam menjaga kontinuitas donatur. Kendala-kendala dalam strategi fundraising juga terlihat pada penerapan prinsip-prinsip fundraising yaitu kurangnya kemampuan untuk meminta masyarakat sebagai wakif, kurangnya kapasitas dalam memperluas relasi dan jaringan, masih minimnya kemampuan dalam menjual produk/program yang ditawarkan, dan sulitnya meningkatkan kepercayaan masyarakat untuk berwakaf di lembaga Global Wakaf Surakarta. Strategi yang dapat dilakukan guna menghadapi kendala-kendala fundraising di Global Wakaf Surakarta adalah dengan memperhatikan unsur-unsur fundraising yaitu dengan pemenuhan kebutuhan wakif, pengembangan produk (programprogram), promosi dengan jangkauan yang lebih luas, dan maintance atau perbanyak donatur tetap agar program yang belum berjalan segera terlaksana.